Penerapan Analisis Regresi Nonparametrik Spline Truncated pada Pemodelan Faktor-Faktor yang Mempengaruhi Tingkat Pengangguran Terbuka di Provinsi Jawa Barat - Zulkifli Rais; Ruliana; Mukhtazam Aqil Mukhtar (Program Studi Statistika Fakultas MIPA UNM, 2024)
Unemployed is someone who has entered the workforce, but does not have a job and is looking for work, setting up a business, and who already has a job but has not yet started working. One indicator that can be used to measure unemployment is The Unemployment Rate. West Java Province is the province in first place with the highest unemployment rate in Indonesia. Based on BPS data, the unemployment rate in West Java Province in 2022 reaches 8.31%. The method that can be used to model factors that are thought to influence the unemployment rate in West Java Province in 2022 is nonparametric spline regression. The nonparametric spline regression method was used in this research because this method is very good at modeling data that has changing patterns at certain intervals. The aim of this research is to get the best model of the factors that influence the unemployment rate and find out what factors significantly influence the unemployment rate in West Java Province in 2022. Based on parameter significance testing, it was found that all the variables used, namely Labor Force Participation Rate, Percentage of Poor Population, District/City Minimum Wage, Government Expenditures, and Average Years of Schooling had a significant effect on TPT in West Java Province in 2022. The value of the determination coefficient obtained was 99.5%.